-9 will make the equation 3x-6/3 = 7x-3/6 true.
Equations are mathematical statements with two algebraic expressions flanking the equals (=) sign on either side. It demonstrates the equality of the relationship between the expressions printed on the left and right sides. We have LHS = RHS (left hand side = right hand side) in every mathematical equation. To determine the value of an unknown variable that represents an unknown quantity, equations can be solved. A statement is not an equation if it has no "equal to" sign. It will be regarded as a phrase.
Given
Equation
3x-6/3 = 7x-3/6
Cross multiplying
6(3x - 6) = 3(7x - 3)
18x - 36 = 21x - 9
21x - 18x = -9 + 36
3x = -27
x = -9
-9 will make the equation 3x-6/3 = 7x-3/6 true.
To learn more about equation, visit:
https://brainly.com/question/10413253
#SPJ1